Kelola Bumi Peduli Ekologi Menurut Kej 1:28 - Stanislaus Surip (Studia Philosophica et Theologica, 2020)
Gen. 1:28 presents the three blessings of God to humans in the form procreation, natural subdue and rule over creatures. These three blessings must be placed in the context of human creation as image and likeness of God (Gen. 1:26-27) so that he becomes his co-worker in cultivating nature and pastoring all His creatures (Gen. 1:28). It was on this purpose that God placed humans in the garden of Eden and gave the task of cultivating and maintaining them (Gen. 2:4-8,15). The Sabbath of God, which became a crown of His creative work, was explored as a model for humans to carry out their missionary work (Gen. 2:1-3). As God rests after six days of work, man must know the limits in cultivating nature and mastering other creatures so as to avoid exploitative greed. The catastrophe of the Flood was the impact of the failure of humans to become partners with God and the presence of the figur of Noah reveals symbolically efforts to preserve the environment or care fo the ecology (Gen. 6-9). The ark that Noah made was like a house, a place to protect and care for all living creatures and their existence was threatened with extinction. Gen. 1:26-28; 2:1-3; 2:4-8,15 and Gen. 6-9 inspire us to care about ecology. Kej 1:28 memaparkan tiga berkat Allah kepada manusia yang berupa prokreasi, penaklukan alam dan penguasaan makhluk-makhluk ciptaan lainnya. Ketiga berkat itu harus ditempatkan pada konteks penciptaan manusia sebagai gambar dan rupa Allah (Kej 1:26-27) sehingga menjadi rekan kerja-Nya dalam mengolah alam dan menggembalakan segenap makhluk ciptaan-Nya (Kej 1:28). Atas tujuan inilah Allah menempatkan manusia di taman Eden dan memberi tugas mengusahakan dan memeliharanya (Kej 2:4-8,15). Sabat Allah yang menjadi mahkota karya penciptaan-Nya pun dieksplor sebagai model bagi manusia dalam menjalani karya misinya (Kej 2:1-3). Sebagaimana Allah beristirahat setelah enam hari berkarya demikianlah manusia harus tahu batas dalam mengolah alam dan menguasai makhluk ciptaan lainnya sehingga terhindar dari kerakusan yang eksploitatif. Malapetaka Air Bah adalah dampak dari gagalnya manusia menjadi rekan kerja Allah dan kehadiran figur Nuh menyingkapkan secara simbolis upaya pemeliharaan lingkungan atau peduli ekologi (Kej 6-9). Bahtera yang dibuat Nuh ibarat sebuah rumah, tempat perlindungan dan pemeliharaan segala makhluk yang hidup dan keberadaannya terancam kemusnahan. Kej 1:26-28; 2:1-3; 2:4-8,15 dan Kej 6-9 menginspirasi kita untuk peduli ekologi.